Kenal Hardware: Media Pembelajaran Pengenalan Perangkat Keras Komputer Menggunakan Teknologi Augmented Reality Berbasis Android - Hendriyana, Hendriyana; Fuada, Syifaul; Pradeka, Deden (Forum Kerjasama Pendidikan Tinggi, 2022)
The Industrial Revolution 4.0 marked by using information and communication technology as a tool that can improve the quality of human activities. This phenomenon is also applied to efficiency of various sectors of human activities are education sector, e-commerce, health, industry, transportation and other sectors. The implementation of technology in the education through android-based learning media can create interactive and interest for students and in the industrial sector used as a marketing tool that can reach market than conventional methods. Augmented Reality (AR) is an interactive technology combines objects in the real world and virtual as visually and real time which generates information. The author implements AR in universities on computing school, especially computer hardware. Hardware characters have different structures, different functional tasks and costs. Through an AR technology called kenal hardware, hopefully the learning interaction process will be more interactive, efficient and cost-effective. The evaluation used to validate the system using a blackbox model by developers and users with four instruments includes functional requirements (91.84%), ease of use (63.27%), errors (24.49%) and interfaces (42.86%). The results of the evaluation indicate that kenal hardware can be used in learning activities to introduce computer hardware